ANALISIS TPACK PADA GURU PROFESIONAL DI SD TUNGGULSARI II SURAKARTA - Insani, Putri Nur; Sayekti, Ika Candra (STIT AL MULTAZAM, 2023)
Technological Pedagogical Content Knowledge (TPACK) is considered an effective theoretical framework for understanding teachers' knowledge in integrating technology. The use of technology-based learning media really helps students to increase their interest in learning and student learning outcomes. This research aims to describe the TPACK possessed by teachers at nggulsari II elementary school, Surakarta. The method used in this research is a qualitative method with a case study research design. The subjects in this research were class III, IV, V teachers. Data collection was obtained through interviews, observation and documentation. The validity of the data in research uses triangulation techniques. The data analysis techniques used are: 1) data collection; 2) reduction; 3) presentation; and 4) drawing conclusions. The results of this research contain seven components and each has its own findings, these components are: (PK) teachers teach using a scientific approach, problem based learning model and discussion and question and answer methods. (CK) the teacher has been able to master the material in each subject taught. (TK) teachers use technology such as LCDs, laptops, student worksheets on Google Drive, YouTube and Power Point when learning in class. (PCK) teachers prepare lesson plans before teaching and teach according to existing KD. (TCK) teachers use learning media such as YouTube and Power Point to explain theories in learning. (TPK) assessment carried out by the teacher through assignments and quiz questions displayed in front of the class using a projector. (TPACK) most teachers do not know this term but in learning it has been implemented. The teacher already has the seven components of TPACK when teaching in class. It's just that teachers at Tunggulsari II Elementary School, Surakarta, don't know more about the meaning of TPACK.